Intergroup trust as a mediator between compassion and positive attitudes toward sexual minorities - Kuglerová, Nikoleta; Popper, Miroslav; Poslon, Xenia Daniela (Frontiers in Psychology, 2022)
Nurturing compassion is not only beneficial for one’s well-being in terms of feelings and cognitions directed towards oneself, but it can also have positive effects on attitudes towards other people through associated humanity and recognition of the universality of suffering. Having compassion towards others may be particularly beneficial in intergroup relations, as minority and stigmatised groups often experience a lack of compassion from the majority. The present study (N = 244) examines the relation between self-compassion, compassion towards others, and the level of trust and positive attitudes toward members of sexual minorities. The results of path analysis suggest that the relationship between compassion for others and attitudes towards people belonging to sexual minorities is mediated by intergroup trust. Fostering compassion could therefore play an important role in increasing trust and improving attitudes towards the people belonging to stigmatised minorities.